2013
DOI: 10.1016/j.cub.2013.08.043
|View full text |Cite
|
Sign up to set email alerts
|

Budding Yeast Escape Commitment to the Phosphate Starvation Program Using Gene Expression Noise

Abstract: Cells must rapidly adapt to changes in nutrient availability. In budding yeast, limitation of phosphate rapidly induces the expression of the Pho regulon genes [1-4]. This starvation program depends on the transcription factor Pho4, which translocates to the nucleus within minutes when cells are transferred to a low-phosphate medium [5]. Contrasting its rapid induction, we report that the Pho regulon can remain induced for dozens of generations in cells transferred back to high phosphate levels. For example, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 33 publications
4
38
0
Order By: Relevance
“…Several studies have implicated enzymes of polyP metabolism in the onset and stabilization of the yeast phosphate starvation program, the PHO pathway (1,7,57). Consistent with this, we found that de-regulation of VTC5 expression alters activation of the PHO pathway.…”
Section: Vtc5 Is a Novel Subunit Of The Polyphosphate Polymerasesupporting
confidence: 89%
“…Several studies have implicated enzymes of polyP metabolism in the onset and stabilization of the yeast phosphate starvation program, the PHO pathway (1,7,57). Consistent with this, we found that de-regulation of VTC5 expression alters activation of the PHO pathway.…”
Section: Vtc5 Is a Novel Subunit Of The Polyphosphate Polymerasesupporting
confidence: 89%
“…Since cell-to-cell variability in gene expression underlies important phenotypic phenomena such as persistence (Balaban et al 2004), competence (Maamar et al 2007), latency (Dar et al 2014), metastasis (Lee et al 2014), responsiveness to fluctuating environments (Acar et al 2005(Acar et al , 2008Blake et al 2006;Kaufmann et al 2007;Levy et al 2012;Vardi et al 2013), and triggering of meiosis (Nachman et al 2007), our results suggest that the probability and efficiency of these processes will be tightly coupled to environmental conditions, with potential evolutionary implications. Gene expression noise is higher at lower growth rates.…”
mentioning
confidence: 90%
“…Synthesis and degradation of polyP are required to buffer cytosolic P i concentration, and this is essential for cells in order to adapt to changing phosphate availability in the environment. That cells actively regulate cytosolic P i is also underscored by the existence of a dedicated transcriptional program, the phosphate signal transduction (PHO) pathway (Thomas and O'Shea, 2005;Vardi et al, 2013), which responds to cytosolic P i levels. Since polyP metabolism does not only respond to cytosolic P i concentration but can even set it (Desfougeres et al, 2016a), the exploration of polyP synthesis and turnover is crucial for understanding P i metabolism and nutrient signaling in general.…”
Section: Introductionmentioning
confidence: 99%